PERAN INTENSITAS KOMUNIKASI TERHADAP KOMITMEN PERNIKAHAN PADA PASANGAN MUSLIM LONG DISTANCE MARRIAGE - Jalal, Novita Maulidya (Indonesian Journal of Islamic Studies (IJIS), 2025)
Long distance marriage, commonly known as long distance marriage, is a type of relationship where married couples live geographically apart, often in different cities, countries, or even continents. This study aims to determine whether there is a role of communication intensity on marital commitment among moeslem couples in long distance marriages. This research employs a quantitative method with communication intensity as the independent variable and marital commitment as the dependent variable. The subjects of this study are 30 individuals experiencing long distance marriage. Data were collected using Likert scales, specifically the communication intensity scale and the marital commitment scale. The obtained data were analyzed using simple regression techniques. The results of this study indicate a significant relationship between marital commitment and communication intensity. The implications of this research can help couples in long distance marriages prioritize communication and strengthen their commitment to marriage despite being geographically separated